Java for dummies - Burd, Barry (Hoboken, N.J. : Wiley, 2011)
-- will enable even novice programmers to start creating Java applications quickly and easily.
pt. 1. Getting started -- pt. 2. Writing your own Java programs -- pt. 3. Working with the big picture : object-oriented programming -- pt. 4. Savvy Java techniques -- pt. 5. The part of tens.
Print version record.
Keywords: Java (Computer program language); Internet programming; Programming languages (Electronic computers); Java (Computer program language); Internet programming; Electronic books